PERIHAL SUFISTIK DALAM NOVEL BEKISAR MERAH KARYA AHMAD TOHARI: SEBUAH PENDEKATAN SEMIOTIKA - Widodo Widodo; Rusdian Noor Dermawan (Universitas Sarjanawiyata Tamansiswa, 2018)
This research aims to describe: (1) the significance of Bekisar Merah based on the Riffaterre semiotics approach and (2) the sufistic matter in the novel Bekisar Merah. This research is a qualitative research. Data of this study are narrative and/or dialogue in the novel which refers to the concept used as an analytical device, namely sufism. The narrative and dialogue are materialized in the clauses, sentences, and paragraphs form. Source of primary data used in this research is the novel Bekisar Merah by Ahmad Tohari. Researchers act as research instruments. To acquire data from primary source, this study uses observation as one of the data collection method, especially reading technique. This study also uses documentation methods in order to acquire and collect data from other relevant referral sources. This study uses hermeneutic methods and using data analysis techniques formulated by Miles & Huberman. After Bekisar Merah was analyzed based on Riffaterre's semiotics approach with a sufism perspective, several conclusions were found. (1) Semiotically, in Bekisar Merah, there are only two types of indirect expression with sufistic nuance, namely displacement of meaning and distorting of meaning. The matrix of Bekisar Merah is eling, especially eling in the context of revisionist neosufism. The matrix is transformed into model (characters), and the model is transformed into variants (nonverbal actions, verbal actions and mental actions in the form of thoughts or feelings). Bekisar Merah’s hypogram is Suluk Wujil. Intertextual pattern relations of Bekisar Merah-Suluk Wujil is innovation, takes place in at least four literary dimensions (content, form, symbolism and character). (2) The matter of sufism philosophy, ethics, and methods is conveyed by indirect delivery. Its medium is the structure, that is the instrinsic novel elements: characters and characterizations, plots, and—in small portions—setting.